ChemInform Abstract: An Iodine‐Catalyzed Hofmann—Loeffler Reaction. Issue 45 (November 2015) - Martinez, Claudio; Muniz, Kilian
Abstract A unique oxidative amination of saturated hydrocarbons that combines a light initiated radical chain reaction with iodine catalysis is presented.